Intraglandular transplantation of adipose-derived stem cells combined with platelet-rich fibrin extract for the treatment of irradiation-induced salivary gland damage - Wang, Zhifa (Exp Ther Med, 2018)
The aim of the present study was to determine the effect of adipose-derived mesenchymal stem cells (ADSCs) combined with heterologous platelet-rich fibrin extract (PRFe) on irradiation-induced salivary gland (SG) damage. ADSCs were isolated from C3H mice, whereas PRFe was obtained from New Zealand rabbits. Twelve weeks post irradiation, the ADSCs or PRFe or their combination were transplanted into the submandibular glands of C3H mice with irradiation-induced damage. The salivary flow rate (SFR) was determined and histopathological analysis was performed at 12 weeks post transplantation. Immunofluorescence, microvessel density measurements and transmission electron microscopy were performed to assess α-amylase (AMY) production, apoptosis and microstructural changes in the cells. The administration of ADSCs combined with PRFe increased the SFR at 12 weeks post transplantation, whereas ADSCs alone or PRFe alone failed to do so. The ADSCs+PRFe-treated, irradiated SGs had fewer damaged and atrophied acinar cells, higher AMY levels and an increased microvessel density compared with the untreated irradiated SGs. Moreover, SG tissue from the ADSCs+PRFe group also showed decreased apoptotic and increased proliferative activity compared to that from the irradiated group. In conclusion, ADSCs or PRFe alone did not restore permanent, irradiation-induced damage of SG tissue when used alone, but when used together, they provided effective treatment outcomes.